Performing the self: identity-formation in the travel accounts of nineteenth-century British women in Italy - Sikstrom, H; Hannah Sikstrom (2015)
From the adventures of Odysseus to those of the male Grand Tourist, travel has often been regarded as an important rite of masculine self-fashioning. However, as this thesis argues, travel and travel writing also provided a valuable opportunity for women's self-fashioning: journeys offered women a means of altering themselves, enabling them to assume a novel identity abroad and in text, whether it be a subversive or idealised version of themselves. Drawing upon Judith Butler's and Sidonie Smith's theories of performativity, this thesis investigates Victorian women travel writers' impulse to self-fashioning, and argues for travel writing as a performative act of identity-formation. Drawing on Butler's notion of subversive repetition, this thesis also demonstrates the ways in which the instability of women authors' narrative identities gives them a potential for agency, enabling authors to unsettle prescribed gender boundaries and challenge cultural constructions of femininity. In particular, I examine the constructed textual travel identities of the following nineteenth-century British women: Anna Jameson, Susan Horner, Emily Lowe, and Frances Minto Elliot. I highlight the discursive strategies that these four authors use in order to create certain images of themselves for their readers in their travelogues about Italy, all published (or, in the case of Horner, written) between the years 1826 and 1881. Jameson, Horner, Lowe, and Elliot also reconfigure traditional notions of travel and gender in their travelogues to articulate and perform definitions of selves that are not necessarily exemplary – at least not at first glance. I examine the ways in which these nineteenth-century authors adopt apparently undesirable selfhoods ('ill', 'intellectual', 'unprotected', and 'idle') and turn supposed weaknesses into strengths. This thesis also analyses the significance of Italy for the travel narrators and their self-representation in relation to the peninsula. Italy signalled a meaningful difference from Britain, and these authors represent it as a positive space for healing, intellectual growth, pleasure, fulfilment, and self-determination. The constructed identities of these four authors result in 'travel performances' that aim to persuade readers of the narrators' aptitude for travel and of their especially meaningful attachment to, experience of, and understanding of Italy. This thesis does not only provide a space for voices which have until now been little recognised in contemporary scholarship. It also sheds light on an important form of Victorian women’s writing that was a valuable route towards cultural and intellectual authority and self-empowerment, as well as a means of personal and professional self-fashioning.